Clinical phenotypes and factor VII genotype in congenital factor VII deficiency - Mariani, Guglielmo; Herrmann, Falko H.; Dolce, Alberto; Batorova, Angelika; Etro, Daniela; Peyvandi, Flora; Wulff, Karin; Schved, Jean F.; Auerswald, Günter; Ingerslev, Jorgen; Bernardi, Francesco; for the International Factor VII Deficiency Study Group (see appendix) (Thrombosis and Haemostasis, 2005)
To investigate the relationship between clinical phenotype, clotting activity (FVIIc) and FVII genotype, a multi-center study of factor VII (FVII) congenital deficiency with centralized genotyping and specific functional assays was carried out. FVII mutations characterized in patients (n=313) were extremely heterogeneous (103 different, 22 novel). Clinical phenotypes ranged from asymptomatic condition, including 15 homozygotes and 14 double heterozygotes, to patients with a severe disease char-acterized by life-threatening and disabling symptoms (CNS, GI bleeding and hemarthrosis) strongly associated with an early age of presentation. Based on type and number of symptoms we classified 90 'severe' (median FVIIc 1.4%, IQR [Interquartile Range] 0.9–3.8), 83 'moderate' (FVIIc 3%, IQR 1–21.7), and 140 'mild' bleeders (FVIIc 14%, IQR 3–31). The significantly different FVIIc levels, and the decreasing prevalence of homozygotes or double heterozygotes among severe (98%), moderate (84%) and mild (56%) bleeders, further support our classification. The excess of females among moderate bleeders (female/male ratio =2.6) is attributable to menorrhagia. There was no evidence for modulation of clinical features by frequent functional polymorphisms. Homozygotes for the same mutation (Ala294Val; 11125del C) with similar FVIIc and FXa generation levels, showed striking differences in clinical phenotypes. Our study depicts the ample clinical picture of this rare disorder, proposes a severity classification and provides arguments for the early management of the disease in the severe cases. Genotype-phenotype relationships indicate the presence of major environmental and/or extragenic components modulating expressivity of FVII deficiency.
Keywords: Bleeding disorders; FVII deficiency; bleeding symptoms; gene mutations; polymorphisms